Strategic Management of People, Retention Strategy of Professionals and Organizational Commitment in a Remote Organizational Structure - Leite, Nildes Raimunda Pitombo; Albuquerque, Lindolfo Galvão de (Revista de Administração da UFSM, 2013)
The main objective of this paper is to analyze the characteristics of the strategic people management, the strategy of retention of professional and of obtaining of organizational commitment, by taking up basis the case of Caulim da Amazônia S.A. – CADAM/Pará Pigmentos S.A. – PPSA and seeking to answer the question: what are the characteristics of the strategic management of people, focusing on retention strategy of professional and obtaining of organizational commitment in their peculiarities of remote organizational structure? The research subjects are directors, managers, HR professionals, supervisors and coordinators of units Ipixuna, Monte Dourado and Barcarena, located in northern region of Brazil, for a total of thirty-six respondents. The results show, at the interfaces of the three units, traits that unite people in all these places and around the same purpose: to retain talented professionals. One could say that, it becomes possible to identify the peculiarities that leads to commitment of people with the organizational objectives, these organizational structures, from the strategic approach of people management. The retention of professionals is conditioned on adaptive capacity of these professionals and their families in these regions.